Pd on the Composite of Perlite and Allylamine-N-isopropylacrylamide Copolymer: A Thermo-Responsive Catalyst for Hydrogenation of Nitroarenes under Mild Reaction Condition - Neda Abedian-Dehaghani (MDPI AG, 2021)
A novel thermo-responsive catalyst for the hydrogenation of nitroarenes under mild reaction condition was devised. To prepare the catalyst, a thermo-responsive polymer was first synthesized through the co-polymerization of N-isopropylacrylamide and allylamine and then covalently grafted on the Cl-functionalized perlite. The resulting composite was subsequently utilized as a support for the stabilization of Pd nanoparticles. Investigation of the catalytic activity of the catalyst approved its high catalytic activity at a temperature above the lower critical solution temperature. More precisely, 0.03 g of the catalyst can promote the reaction of 1 mmol of nitro-compounds in H2O/EtOH (1:1) at 45 °C to furnish the corresponding products in 70–100% yields. This issue was assigned to the collapse of the polymeric component and formation of a hydrophobic environment that was beneficial for the mass-transfer of the hydrophobic nitroarenes. Notably, the catalytic activity of the catalyst was higher than that of palladated perlite and thermos-responsive polymer due to the synergistic effects between the perlite and polymeric moiety. Furthermore, the study of the substrate scope confirmed that a wide range of substrates with different steric and electronic properties could tolerate hydrogenation reaction. Moreover, the catalyst was highly selective toward hydrogenation of the nitro group and could be recycled up to seven runs with insignificant Pd leaching and loss of catalytic activity. The hot filtration test also confirmed the heterogeneous nature of the catalysis.